Investigation of microcystin conformation and binding towards PPP1 by molecular dynamics simulation. (5th January 2022) - Jaeger-Honz, Sabrina; Nitschke, Jahn; Altaner, Stefan; Klein, Karsten; Dietrich, Daniel R.; Schreiber, Falk
Abstract: Microcystins (MC) are a group of structurally similar cyanotoxins with currently 279 described structural variants. Human exposure is frequent by consumption of contaminated water, food or food supplements. MC can result in serious intoxications, commensurate with ensuing pathology in various organs or in rare cases even mortality. The current WHO risk assessment primarily considers MC-LR, while all other structural variants are treated as equivalent to MC-LR, despite that current data strongly suggest that MC-LR is not the most toxic MC, and toxicity can be very different for MC congeners. To investigate and analyse binding and conformation of different MC congeners, we applied for the first time Molecular Dynamics (MD) simulation to four MC congeners (MC-LR, MC-LF, [ Enantio -Adda5]MC-LF, [ β -D-Asp3, Dhb7]MC-RR). We could show that ser/thr protein phosphatase 1 is stable in all MD simulations and that MC-LR backbone adopts to a second conformation in solvent MD simulation, which was previously unknown. We could also show that MC congeners can adopt to different backbone conformation when simulated in solvent or in complex with ser/thr protein phosphatase 1 and differ in their binding behaviour. Our findings suggest that MD Simulation of different MC congeners aid in understanding structural differences and binding of this group of structurally similar cyanotoxins. Highlights: Molecular Dynamics (MD) Simulations of MC-LR and three MC congeners were performed. A second backbone conformation of MC-LR in solvent previously unknown was found. Different conformations and binding behaviour of MC congeners were identified.